2022
DOI: 10.3390/s22218296
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Guided Waves for Liquid Water Localization in Fuel Cells: An Ex Situ Proof of Principle

Abstract: Water management is a key issue in the design and operation of proton exchange membrane fuel cells (PEMFCs). For an efficient and stable operation, the accumulation of liquid water inside the flow channels has to be prevented. Existing measurement methods for localizing water are limited in terms of the integration and application of measurements in operating PEMFC stacks. In this study, we present a measurement method for the localization of liquid water based on ultrasonic guided waves. Using a sparse sensin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
0
0
Order By: Relevance
“…This measurement principle has been demonstrated in ex-situ experiments on a single bipolar plate in a temperature-controlled lab environment [2]. For an integration of the sensor system in an operating PEMFC, the changing environmental and operational conditions must be considered.…”
Section: Fig 1 Scheme Of the Measurement Principle Ultrasonic Guided ...mentioning
confidence: 99%
See 1 more Smart Citation
“…This measurement principle has been demonstrated in ex-situ experiments on a single bipolar plate in a temperature-controlled lab environment [2]. For an integration of the sensor system in an operating PEMFC, the changing environmental and operational conditions must be considered.…”
Section: Fig 1 Scheme Of the Measurement Principle Ultrasonic Guided ...mentioning
confidence: 99%
“…The resulting difference signal is divided into 500 windows before calculating the normalized signal energy Ed for each window. It has been shown that the resulting signal feature vector is suitable to localize single water drops on the bipolar plate using data-driven modelling [2]. Here, the same signal feature is used to quantify the influence of different conditions on the measurement.…”
Section: Investigation Of Operational Conditionsmentioning
confidence: 99%
“…a droplet, will lead to reflection or attenuation of the incident wave [29]. In a recent work, a tomographic water droplet localization scheme is implemented using Lamb waves crossing the entire flow field in different directions [30], in which a localization precision of approx. 4 mm in case of a single 5 µL droplet was realized.…”
mentioning
confidence: 99%